Supervisi Berbasis Penelitian Tindakan Sekolah - Mar-Atin Nabila Rohmah; Ana Muslimah; Meti Fatimah (TSAQOFAH, 2026)
Educational supervision is an important strategy for improving teacher professionalism and the quality of learning in schools. However, its implementation is still frequently oriented toward administrative assessment and has therefore not been able to provide optimal solutions to learning problems. This study aims to examine the concept of School Action Research (PTS)-based supervision, the relationship between supervision and PTS, its implementation stages, and its benefits in improving the quality of education. The study employed a qualitative approach using the library research method. Data were obtained from various secondary sources, including books, scholarly journal articles, proceedings, and relevant laws and regulations, and were subsequently analyzed using content analysis. The results of the review indicate that PTS-based supervision integrates the teacher development process with systematic research activities through the stages of planning, action implementation, observation, evaluation, reflection, and follow-up. This approach helps teachers identify and resolve learning problems based on data while encouraging the development of a reflective, collaborative, and innovative school culture. This study concludes that PTS-based supervision can serve as an effective strategy for improving teachers’ professional competence, the quality of the learning process, and the quality of education on an ongoing basis. These findings provide a conceptual contribution to the development of academic supervision and practical implications for school principals and supervisors in implementing systematic, data-based teacher development oriented toward continuous improvement.